Immediate effect of intensive atorvastatin therapy on lipid parameters in patients with acute coronary syndrome - Vondrakova, Dagmar; Ostadal, Petr; Kruger, Andreas (Lipids in health and disease, 2010)
BACKGROUND: Intensive statin therapy decreases mortality and incidence of coronary events in patients after acute coronary syndrome (ACS). Recently it has been reported that spontaneous lipid levels remain clinically stable during ACS. The immediate influence of lipid levels by high-dose statin therapy initiated at admission in ACS patients is, however, not clear. METHODS: We have analyzed a group of 114 patients with ACS (mean age 63.7; females 25.4%). Atorvastatin 80 mg was administered at admission and then once daily for the rest of hospitalization. The levels of total cholesterol (TC), LDL-cholesterol (LDL), HDL-cholesterol (HDL), and triglycerides (TG) were measured at admission (D0), and then every morning of hospitalization (D1, D2). RESULTS: The mean entry values (D0) of TC, LDL, HDL and TG (in mmol/L) were 5.24, 3.26, 1.07 and 1.31, respectively. The therapy with atorvastatin 80 mg resulted in a decrease of TC levels in the first morning (D1) by 6.1% and in the second morning (D2) by 13.2% (p<0.001 for all comparisons with the entry value D0); LDL was decreased by 5.8% (D1) and 15.6% (D2) (p<0.001 vs. D0); the level of HDL was decreased by 7.5% (D1) and 12.1% (D2) (p<0.001 vs. D0). In contrast, the TG level was higher in the first morning (D1) by 20.6% and in the following morning (D2) by 25.5% (p<0.05 vs. D0). CONCLUSIONS: We have shown that intensive statin therapy started at admission in ACS patients has a highly significant, immediate effect on all monitored lipid levels. Since TC and LDL levels were decreased as predicted, reduction in HDL and increase in TG levels suggest a different acute effect of high-dose statin on lipid levels in comparison with long-term treatment of ACS patients.
Keywords: Cholesterol, LDL; lipidy; Triglycerides; hypercholesterolemie; lidé; Middle Aged; mužské pohlaví; Cholesterol; kyseliny heptylové; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Pyrroles; Atorvastatin; Heptanoic Acids; Lipids; ženské pohlaví; Humans; statiny; triglyceridy; lidé středního věku; atorvastatin; HDL-cholesterol; LDL-cholesterol; akutní koronární syndrom; Hypercholesterolemia; Female; Cholesterol, HDL; Acute Coronary Syndrome; pyrroly; Male; cholesterol